Profiling older Malaysians using three-tier economic wellbeing measure based on netflow-networth typologies - Chan, Benjamin Yin Fah (2012)
The study aims to profile older Malaysians using three-tier economic wellbeing measure based on netflow-networth typologies. The study utilized secondary data from an IRPA Project titled “Economic and Financial Aspects of Ageing in Malaysia (2005)”, one of the research project under the Quality of Life of Older Malaysians research program. A total of 2,327 older persons in Malaysia were interviewed in this cross-sectional study. The study found that 77 per cent of the respondents had positive net flow (mean monthly income of RM 574 and mean expenses of RM 213). Eighty-two percent of them has a positive net worth (mean assets = RM 90,993; mean liabilities =RM 15,302). For perceived income adequacy, 63 percent of them perceived their income as adequate while the remaining 37 per cent perceived their income was not adequate for daily expenses. The economic wellbeing of older Malaysians in this study was determined by combining both objective measures (net flow, net worth) and subjective measures (perceived income adequacy). Three levels of economic wellbeing were identified namely, (1) economically advantaged, (2) at risk and, (3) economically disadvantaged. In this study, 26 per cent of them were grouped into economically disadvantaged group, 49 per cent in at risk group and 25 per cent in economically advantaged group. Multinomial Logistics Analysis revealed that male was 1.25 times more likely than female to be in the advantaged group over the at risk group. Those who were working, financial prepared, good self-rated health were 1.3 times more likely to be in the advantaged group over the at risk group. Since the economically disadvantaged group has been taken care by many poverty eradication programs in Malaysia, efforts should be focused on the at risk group, with is in lines with the Malaysia Economic Transformation Programme (ETC) to uplift the quality of life of lower income households. In order to increase the level economic wellbeing, financial education programs should be introduced to both older and younger persons to enable them to make effective financial decisions for present and future needs.